Mechanistic insights on anticancer drugs with specific biological targets and signalling pathways - Mohsina Patwekar; Faheem Patwekar; Anuradha Medikeri; Shaikh Daniyal; Mohammad A. Kamal; Gulzar Ahmed Rather; Rohit Sharma (Open Exploration Publishing Inc., 2023)
Complex enzyme interactions play a role in the spread of cancer, a process fueled by unregulated cell proliferation. DNA topoisomerases, which are important for fixing DNA topological problems, have drawn a lot of interest as potential targets for anti-cancer medications. Cancer treatment, which includes radiation, surgery, and chemotherapy, tries to control cell survival, demise, and mobility, which are mediated by ion transportation across cell membranes via channels and carriers. The malignant transition is characterised by altered channels and carriers. Chemoresistance, which commonly develops after chemotherapy, denotes decreased therapeutic effectiveness against cancer progression. Chemosensitizers are used in combination with anti-cancer medications to overcome this resistance, particularly against adenosine triphosphate (ATP)-binding cassette (ABC) transporters including P-glycoprotein, multidrug resistance-associated protein 1 (MRP1), breast cancer resistance protein (BCRP). Effective targets for treatment are transcription factors, which play a key role in the development of cancer. With the use of interactions with receptors, enzymes, ion channels, transporters, and TFs, nanotechnology improves the safety of tumour localization, treatment, and diagnostics. As a result of mutations or altered signalling, rat sarcoma (RAS) proteins regulate signalling, which is essential for both healthy growth and the development of cancer. Rational treatments that target RAS pathways have the potential to inhibit the growth and spread of tumours. New treatments are still being developed, and they are showing promise in clinical settings. The roles of receptors on tumour cells, their significance for cancer therapy, and recent advancements in preclinical and clinical research are all included in this overview.